The reality of organizational isolation in the public sector in Saudi Arabia - Alareifi, Hussah Mohammed; Alshenaifi, Najla Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to identify the reality of organizational isolation in the public sector in the kingdom of Saudi Arabia and to find out its causes, effects and methods of treatment, through the selection of a random sample of (453) administrative and administrative in various public sectors in the kingdom of Saudi Arabia. This study used the descriptive statistics scale and the questionnaire as a data collection tool and relied on the statistical package program (SPSS), through the Cyberman correlation coefficient, iterations, Alpha-krubach, and arithmetic averages. In this study, we came to a set of results, the most important of which are the following: there is no organizational isolation in the public sector in the kingdom of Saudi Arabia in the dimension of social support and friendships with co-workers and after emotional deprivation, while the study proved the existence of moderate organizational isolation in the dimension of performance evaluation. In this study, we found that most of the effects of regulatory isolation are not present in the public sector in Saudi Arabia. We also found that many methods of reducing organizational isolation are actually applied in the public sector in the kingdom of Saudi Arabia. The study recommended the following: the management should pay attention to social and cultural programs that enhance communication between employees, and therefore reflected on their mental health and relationships with their colleagues.
Keywords: Isolation; Organizational; Public sector